Is exposure to ionising radiation associated with childhood cardiac arrhythmia in the Russian territories contaminated by the Chernobyl fallout? A cross-sectional population-based study. Issue 3 (25th March 2018) - Jourdain, Jean-Rene; Landon, Geraldine; Clero, Enora; Doroshchenko, Vladimir; Silenok, Aleksandr; Kurnosova, Irina; Butsenin, Andrei; Denjoy, Isabelle; Franck, Didier; Heuze, Jean-Pierre; Gourmelon, Patrick
Abstract : Objective: To investigate childhood cardiac arrhythmia and chronic exposure to caesium-137 ( 137 Cs) resulting from the Chernobyl accident. Design: Prospective cross-sectional study using exposed/unexposed design conducted in the Bryansk region from May 2009 to May 2013 on children selected on the basis of 137 Cs soil deposition: control territories ([ 137 Cs]<37 kBq per square metre, where children were considered as unexposed) and contaminated territories ([ 137 Cs]>555 kBq per square metre, where children were considered as exposed). Setting: Russian territories affected by the Chernobyl fallout (Bryansk region). Participants: This cross-sectional study included 18 152 children aged 2–18 years and living in the Bryansk region (Russia). Main outcome measures: All children received three medical examinations (ECG, echocardiography and 137 Cs whole-body activity measurement) and some of them were given with a 24-hour Holter monitoring and blood tests. Results: Cardiac arrhythmia was diagnosed in 1172 children living in contaminated territories and 1354 children living in control territories. The crude prevalence estimated to 13.3% in contaminated territories was significantly lower than in control territories with 15.2% over the period 2009–2013 (P<0.001). Considering 137 Cs whole-body burden as exposure, cardiac arrhythmia was found in 449 contaminated children and 2077 uncontaminated children, corresponding to an estimated crude prevalence of 14.5% and 14.2%, respectively, which does not differ significantly (P=0.74). Also, we investigated the association between territory, exposure to 137 Cs and cardiac arrhythmia: the adjusted OR was not significant (0.90 with 95% CI 0.81 to 1.00; P=0.06) for the territory. For 137 Cs whole-body burden, the ORs close to 1 did not reach statistical significance (P for trend=0.97). Conclusion: This study does not observe an association between cardiac arrhythmia and 137 Cs deposition levels in the Bryansk region exposed to Chernobyl fallout. The suspected increase of cardiac arrhythmia in children exposed to Chernobyl fallout is not confirmed.